Association of blood cadmium and physical activity with mortality: A prospective cohort study - Yilin Chen; Cien Zhen; Lin Zeng; Hongliang Feng; Jinyu Wang; Qi Yong H. Ai; Sizhi Ai; Jihui Zhang; Yannis Yan Liang; Huachen Xue; Yujing Zhou (Ecotoxicology and Environmental Safety)
Physical activity (PA) may be considered an alternative method to ameliorate the elevated mortality risks associated with cadmium exposure. In this prospective cohort study, a total of 20,253 participants (weighted mean age, 47.79 years), including 10,247 men (weighted prevalence: 50.1 %), aged 18 years or older, were selected from the National Health and Nutrition Examination Survey from 2007 to 2018. Multivariable Cox proportional hazards regression models were utilized to evaluate the associations between blood cadmium levels, PA, and the risks of mortality. Restricted cubic spline analyses were employed to investigate the nonlinear relationships between blood cadmium and PA levels and mortality risks. During a median follow-up of 7.6 years, a total of 2002 (9.89 %) all-cause deaths occurred, of which 581 (2.87 %) participants were due to cardiovascular disease (CVD) and 498 (2.46 %) died of cancer. J-shaped associations were observed for blood cadmium with risks of mortality (all P overall < 0.001; all P nonlinearity < 0.001). Blood cadmium and PA had multiplicative interactions on mortality risk (all P interaction < 0.05). Compared with the subgroup with the lowest quartile of blood cadmium and recommended PA, the combination of the highest quartile of blood cadmium and without recommended PA was associated with the highest risks of all-cause and cancer mortality, followed by those meeting recommended PA but in the highest quartile of blood cadmium (hazard ratios, 2.43; 95 % confidence interval, 1.95–3.02). Achieving recommended PA significantly attenuated the detrimental effects of blood cadmium on all-cause, CVD, and cancer mortality risks.